PEMETAAN FAKTOR RISIKO RAWAN GIZI PADA ANAK MENGGUNAKAN MODEL GWR BERBASIS SIG DI KABUPATEN PASAMAN BARAT - Khairani, Annisa; Purwaningsih, Endah (DEPARTEMEN GEOGRAFI FIS UNP, 2025)
This studies has the objective of mapping hazard factors for dietary vulnerability in children in West Pasaman Regency in 2020. The studies method used become quantitative studies. The information used is secondary information in the form of statistics on the percentage of stunting patients with chance factors in the shape of information on one of a kind Breastfeeding to kids and information on proper sanitation. The consequences of this study are a map of the hazard factors that dominate the reasons of stunting based on control using the Geographically Weighted Regression version, in which the consequences of the map with ArcGIS software have a completely excessive impact of the unbiased variables based totally on the results of speculation checking out using a massive test of t fee <0.5 the use of the variable receiving extraordinary Breastfeeding in youngsters and right sanitation. Keywords: Nutritional Prone, Stunting, Geographically Weighted Regression, GWR